2023
DOI: 10.48550/arxiv.2301.02529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental quantum imaging distillation with undetected light

Abstract: Imaging based on the induced coherence effect makes use of photon pairs to obtain information of an object without detecting the light that probes it. While one photon illuminates the object, only its partner is detected, so no measurement of coincidence events are needed.The sought-after object's information is revealed observing a certain interference pattern on the detected photon. Here we demonstrate experimentally that this imaging technique can be made resilient to noise. We introduce an imaging distilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Several recent works have demonstrated that quantum-correlated light can overcome certain limitations in conventional holography. Töpfer et al (3) and Fuenzalida et al (4) used frequencycorrelated beams to illuminate the object with a different wavelength than the detected light. Similarly, Chrapkiewicz et al (5) showed that Hong-Ou-Mandel interference between two single photons enables holography without needing phase stability.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent works have demonstrated that quantum-correlated light can overcome certain limitations in conventional holography. Töpfer et al (3) and Fuenzalida et al (4) used frequencycorrelated beams to illuminate the object with a different wavelength than the detected light. Similarly, Chrapkiewicz et al (5) showed that Hong-Ou-Mandel interference between two single photons enables holography without needing phase stability.…”
Section: Introductionmentioning
confidence: 99%